Pembuatan Katalis Pd-Ce/γ –Al2O3 dan Uji Aktivitas terhadap Oksidasi Metana - Suseno, Ahmad; Triyono, Triyono; Setiaji, Bambang (Jurnal Kimia Sains dan Aplikasi, 1999)
Effects of Ce addition on Pt/γ - Al2O3 catalysts preparation and their catalytic activity on oxidation of methane have been investigated. In this study, the catalysts were prepared by impregnating chloride salt solution of palladium and sulphate salt of cerium on γ-AI2O3 support. Characterization of catalysts was conducted by gas sorption method to determine surface area, pore radius and pore volume. The test of catalytic activity on oxidation of methane was carried out in a flow reactor system at a temperature range from 350°C to 600°C. Products of reaction were analysed by non-dispersive IR spectroscopy. It was observed that the surface area, pore radius and pore volume decrease with the addition of cerium. The results of oxidation process showed that Pd-Ce/γ-Al2O3 catalyst can be used for oxidation of methane up to 90.62% conversion